A Large Along-Track Baseline Approach for Ground Moving Target Indication Using TanDEM-X - Baumgartner, Stefan V.; Krieger, Gerhard; Bethke, Karl-Heinz (International Radar Symposium (IRS), 2007)
In the paper a new method for ground moving target indication using two satellites (i.e. the TerraSAR-X and the TanDEM-X satellite) is presented. For this special method the along-track baseline between the satellites is chosen to be in the order of several kilometres, so that each satellite observes the same moving target at different times. The proposed method allows the estimation of the true broadside position of the moving target with high accuracy as well as the estimation of the ground velocity and acceleration vector without the need of complex bistatic processing techniques.
DLR Import::2019-04-03
Keywords: Along-track interferometry (ATI); Ground moving target indication (GMTI); TanDEM-X; TerraSAR-X